2004
DOI: 10.1002/ajmg.a.30117
|View full text |Cite
|
Sign up to set email alerts
|

Infantile systemic hyalinosis: A clinicopathological study

Abstract: Infantile systemic hyalinosis (ISH) is a presumed autosomal recessive connective tissue condition. Symptoms usually begin at birth or shortly thereafter, and are characterized by pain when handled, painful and swollen joints and, later on, dermal anomalies, diarrhea, failure to thrive and recurrent infections, which usually lead to death around the age of 2. The skin has generally diminished elasticity with small pearly papules appearing on neck, ears, coccygeal region, and face. We present two unrelated patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…It is characterized by the accumulation of amorphous, unidentified hyaline material in the skin and other organs [Fayad et al, 1987;Keser et al, 1999;Landing and Nadorra, 1986] leading to papulonodular skin lesions, gingival hypertrophy, flexion contractures of the joints, large subcutaneous tumors commonly involving the scalp, and osteolytic lesions of the long bones, skull, and distal phalanges [Fayad et al, 1987;Keser et al, 1999] (see also www.orpha.net). Infantile systemic hyalinosis (ISH; MIM] 236490), the most severe form of the disease, leads to death in early childhood, mainly due to severe diarrhea, recurrent infections, and failure to thrive [Criado et al, 2004;Landing and Nadorra, 1986]. Patients afflicted with the milder form of the disease, juvenile hyaline fibromatosis (JHF; MIM] 228600), usually live beyond adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by the accumulation of amorphous, unidentified hyaline material in the skin and other organs [Fayad et al, 1987;Keser et al, 1999;Landing and Nadorra, 1986] leading to papulonodular skin lesions, gingival hypertrophy, flexion contractures of the joints, large subcutaneous tumors commonly involving the scalp, and osteolytic lesions of the long bones, skull, and distal phalanges [Fayad et al, 1987;Keser et al, 1999] (see also www.orpha.net). Infantile systemic hyalinosis (ISH; MIM] 236490), the most severe form of the disease, leads to death in early childhood, mainly due to severe diarrhea, recurrent infections, and failure to thrive [Criado et al, 2004;Landing and Nadorra, 1986]. Patients afflicted with the milder form of the disease, juvenile hyaline fibromatosis (JHF; MIM] 228600), usually live beyond adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…10 Since that time, 34 additional cases have been reported, including a recent review of 19 cases from a referral center in Saudi Arabia. 1,9,11,12,17,23,24 Although ISH is panethnic, it is noted that many cases reported have been of MiddleEastern origin. 1,2,12,15,25 While some of the presumed increased incidence among this population may be attributed to a higher rate of consanguineous relationships, Al-Mayouf et al 2 have suggested a higher underlying carrier frequency in this population.…”
Section: Discussionmentioning
confidence: 95%
“…J AM ACAD DERMATOL VOLUME 58, NUMBER 2 Histologic evaluation of the skin and organ biopsy specimens demonstrated deposits of amorphous hyaline material in the dermis and viscera. 17 The nature of the hyaline material remains unclear 11 ; however, some studies have observed an ultrastructural fibrillogranular material with a banding pattern identical to type VI collagen, a normal dermal component. 12,18 Hyaline deposits in the gastrointestinal tract may lead to diarrhea and protein-losing enteropathy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This syndrome was first described by Nezelof in 1978, and numerous cases have subsequently been documented in the literature. ISH presents with increasing contractures, joint pain, thickened skin, and perianal papules typically within the first 6 months of life 1,4,5. A protein losing enteropathy (PLE) with resultant diarrhea and failure to thrive has been associated with ISH 1,2,4,6.…”
Section: Introductionmentioning
confidence: 99%